Speech and hearing science as related to clinical audiology and speech and language pathology - Oyer, Herbert F; Beasley, Daniel S (Journal of All India Institute of Speech and Hearing)
It is the intent of the authors to comment generally upon the relevance of the discipline of speech and hearing science as the principal substratum upon which the professions of speech and language pathology and audiology are built. This is not meant to deny the importance of other areas that contribute information such as physics, anatomy, neurophysiology, linguistics, or psychology; for in order to explore the important correlates of speech, language, and audition one must call upon information provided for by these disciplines. In a sense, the speech and hearing scientist, if properly prepared, is one who can deal meaningfully with those elements of the other disciplines that bear significantly upon his inquiries into events of speech, language, or audition